Effect of Particle Size on Physico-Chemical and Antioxidant Activity of Insoluble Dietary Fiber Powder from Corncob (Zea mays L.) - Suryanto, Edi; R.I. Taroreh, Mercy (Asian Journal of Chemistry, 2022)
Effects of particles size of dietary fiber powder on the physico-chemical properties and antioxidant activity of corncob were investigated. Corncob was grounded in a regularly mill and grinding characteristics and the particles size were evaluated by particle size analyzer (PSA) using laser diffraction method and Fourier transform infrared (FTIR). The results showed that the insoluble dietary fiber (IDF) powder from corncob had the highest crude fiber content (32.31%) and carbohydrates (55.07%). Spectral analysis shows that the IDF matrix structure does not change after grinding and has three characteristics of absorption spectra at 3433-3425 cm-1 (O-H); 2920 cm-1 (C-H) and 1635 cm-1 (aromatic) in presence of the special structures of polysaccharide and lignin compounds. Particle size analyzer (PSA) results showed that the size of IDF 200 mesh and 80 mesh powder were 63.13 and 260.89 μm, respectively. The insoluble dietary fiber (IDF) significantly shows a decrease in dietary fiber content in line with the reduction in particle size. The IDF powder with a particle size of 63.13 μm showed that highest total phenolic content accompanied with the best antioxidant activity through all antioxidant assays (p < 0.05). This study concluded that the IDF micro-powder particle size exerted influence on physico-chemical properties, dietary fiber, total phenolic and antioxidant activity.